"Before I Settle Down": Youth Travel and Enduring Life Course Paradigms - Amit, Vered (Anthropologica, 2022)
Young Canadians taking up opportunities for extended stays abroad on work or study programs often rep- resent this form of travel as something that you do before you "settle down." In doing so, they are implicitly constructing a version of the life course, also espoused by many contemporary scholars, which allows the phase of youth to be redefined and extended, even while continuing to fix adulthood as the attain- ment of particular roles and statuses. The more that the defi- nition of youth is reworked to accommodate changing roles and transitions, the less pressure there is to redefine the nature of adulthood.